2018
DOI: 10.1111/nmo.13501
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive transcutaneous auricular vagus nerve stimulation prevents postoperative ileus and endotoxemia in mice

Abstract: Background The cholinergic anti‐inflammatory pathway comprises the perception of peripheral inflammation by afferent sensory neurons and reflex activation of efferent vagus nerve activity to regulate inflammation. Activation of this pathway was shown to reduce the inflammatory response and improve outcome of postoperative ileus (POI) and sepsis in rodents. Herein, we tested if a non‐invasive auricular electrical transcutaneous vagus nerve stimulation (tVNS) affects inflammation in models of POI or endotoxemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 63 publications
2
62
0
Order By: Relevance
“…Surgical implantation of vagus nerve pacemakers has demonstrated highly beneficial therapeutical results in rheumatoid arthritis and Crohn's disease (Koopman et al 2016;Bonaz et al 2016). A need for surgery can be circumvented by transauricular vagus nerve stimulation using an external pulse generator, which is an inexpensive device meant for personal use (Hong et al 2019). Furthermore, transcutaneous vagus nerve stimulation reduced systemic HMGB1 levels and improved survival in an experimental sepsis model (Huston et al 2007).…”
Section: The Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…Surgical implantation of vagus nerve pacemakers has demonstrated highly beneficial therapeutical results in rheumatoid arthritis and Crohn's disease (Koopman et al 2016;Bonaz et al 2016). A need for surgery can be circumvented by transauricular vagus nerve stimulation using an external pulse generator, which is an inexpensive device meant for personal use (Hong et al 2019). Furthermore, transcutaneous vagus nerve stimulation reduced systemic HMGB1 levels and improved survival in an experimental sepsis model (Huston et al 2007).…”
Section: The Cholinergic Anti-inflammatory Pathwaymentioning
confidence: 99%
“…In addition to the documented inhomogeneous distribution of sympathetic fibers in the human ear, the territories of the great auricular nerve, which for the most part originates in C3 with contributions from C2 (Becelli et al, 2014), and of the lesser occipital nerve, which mainly originates in C2 with contributions from C3 (Waxenbaum and Bordoni, 2019), reportedly distributes differentially across the cymba concha area (the AVNS zone) among humans. It has further been demonstrated that the Kiernan and Mitchell (1974), Chiu et al (1979), Park and Roh (2002), Liugan et al (2018), Cakmak et al (2018) and Hong et al (2019). cymba concha is innervated by the lesser occipital nerve in a quarter (26%) of participants, which indicates that the same proportion of the experimental groups of AVNS studies may exhibit inhomogeneity (Pantaloni and Sullivan, 2000).…”
Section: Significant Confounding Effects Of Inhomogeneity Problemsmentioning
confidence: 93%
“…The number of auricular vagal nerve stimulation (AVNS) studies in the literature has increased logarithmically over the last two decades (Cakmak, 2006;Badran et al, 2018a,b;Burger et al, 2019;Hong et al, 2019;Zhao et al, 2019). A broad range of clinical conditions across multiple disciplines-from neurology to immunology-have been investigated for a potential clinical therapeutic response to AVNS.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have used cervical VNS, which activates both efferent and afferent signaling. The role of efferent vagus nerve signaling in controlling proinflammatory cytokine release, inflammation, and cardiovascular and metabolic indices has been unequivocally shown (Borovikova et al 2000;Inoue et al 2016;Hong et al 2018b). In addition, activation of afferent vagus nerve signaling has been shown to cause peripheral anti-inflammatory effects (Olofsson et al 2015;Inoue et al 2016).…”
Section: Vagus Nerve Stimulation In Animal Models Of Inflammatory Conmentioning
confidence: 99%
“…Revealing the brain mechanisms of this regulation presents an interesting area for future research. The anti-inflammatory and disease-alleviating efficacy of VNS has been indicated in acute settings of murine endotoxemia, sepsis, hemorrhagic shock, uncontrolled bleeding, postoperative ileus, kidney ischemia-reperfusion injury, and other conditions (Borovikova et al 2000;Guarini et al 2003;de Jonge et al 2005;Inoue et al 2016;Hong et al 2018b). The use of implanted devices for bioelectronic VNS has allowed studying the efficacy of this approach in chronic settings of inflammatory conditions.…”
Section: Vagus Nerve Stimulation In Animal Models Of Inflammatory Conmentioning
confidence: 99%